2016
DOI: 10.1186/s12936-016-1574-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial superglue generates a full-length circumsporozoite protein virus-like particle vaccine capable of inducing high and durable antibody responses

Abstract: BackgroundMalaria, caused by Plasmodium falciparum, continues to have a devastating impact on global health, emphasizing the great need for a malaria vaccine. The circumsporozoite protein (CSP) is an attractive target for a malaria vaccine, and forms a major component of RTS,S, the most clinically advanced malaria vaccine. The clinical efficacy of RTS,S has been moderate, yet has demonstrated the viability of a CSP-based malaria vaccine. In this study, a vaccine comprised of the full-length CSP antigen present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 48 publications
5
51
0
Order By: Relevance
“…We also demonstrated that those conjugates exhibited a range of different functions (Bae et al, ; Choi et al, ; Moon et al, ). The ST/SC protein ligation system has been applied for displaying various antigenic proteins and targeting ligands on VLPs and their effective immune response inductions and cell‐specific gene delivery were successfully demonstrated (Brune et al, , ; Bruun, Andersson, Draper, & Howarth, ; Janitzek et al, ; Kasa, Raneni, Chamoun‐Emanuelli, Wright, & Chen, ; Ke et al, ; Leneghan et al, ; Singh et al, ; Thrane et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that those conjugates exhibited a range of different functions (Bae et al, ; Choi et al, ; Moon et al, ). The ST/SC protein ligation system has been applied for displaying various antigenic proteins and targeting ligands on VLPs and their effective immune response inductions and cell‐specific gene delivery were successfully demonstrated (Brune et al, , ; Bruun, Andersson, Draper, & Howarth, ; Janitzek et al, ; Kasa, Raneni, Chamoun‐Emanuelli, Wright, & Chen, ; Ke et al, ; Leneghan et al, ; Singh et al, ; Thrane et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, when using such modular approaches, the resultant epitope display is directly dependent on the applied conjugation method, as well as the specific surface geometry of the employed CLP backbone. In addition, these technologies allow for separate recombinant production of antigens in various expression systems, ensuring high quality and correct protein processing before CLP conjugation [39][40][41][42]. The different conjugation systems used for modular CLP vaccine development is described in detail elsewhere [43].…”
Section: Modular Antigen Displaymentioning
confidence: 99%
“…The RBD-Catcher coupling efficiency was calculated as percentage conjugation (i.e. number of bound antigens divided by the total available binding sites (=180) per CLP) by densitometric analysis of on the SDS-PAGE gel, using ImagequantTL (as previously described 67 . In parallel, RBDc-CLP was purified by density gradient ultracentrifugation by adding the RBDc-CLP onto an Optiprep™ step gradient (23, 29 and 35%) (Sigma-Aldrich) followed by centrifugation for 3.30h at 47800rpm, as previously described26.…”
Section: Formulation and Purification Of The Rbd-clp Vaccinesmentioning
confidence: 99%